Christian Democrat Internationalism c - Durand, Jean-Dominique; Durand, Jean-Dominique (Peter Lang, 2014)
From September 2011 to December 2013 the Luigi Sturzo Institute in Rome along with the Centre of European Studies planned a series of international scientific meetings to study one highly important political subject: the commitment of Christian Democrats on an international level. This project has been organised thanks to the support of the Konrad Adenauer Stiftung, and the International Labour Organisation. Internationalism is a Key Element for the Christian Democrat Identity. In fact, CD is a political movement of thought and action whose roots lie in a specific ideology: to use the German word Weltanschauung, it is based on a particular framework of ideas and beliefs that leads the party to interpret the relationship between men and nations from an international point of view, ensuring the human being a central place in every social policy. The Chancellor of Germany, Angela Merkel, wrote in a Message to these Meetings: (S0(BWe can consider ourselves very lucky that 50 years ago forward-thinking personalities founded the World Union of Christian Democrats. From then on, the world, through globalisation, has been deeply changed. Events that take place in other continents immediately impact on our lives. We will be able to protect ourselves from terrorism, achieve economic and social security, and defend our environment only through common global action. This is the task of our generation: to overcome these global challenges. [$1! =(B] Our parties and our political organisations share a common Christian ideal of man. This ideal, grounded on the inalienability of human dignity, is at the core of one important value: to this man has linked a social and economic model that combines economic success and social responsibility.(S1 (BHer message clearly shows the need to use historical knowledge, to return to and explore a rich and challenging past as well as to develop a reflection on and a course of action for the present and the future.s